Peran Faktor Sosial dan Lingkungan Dalam Investasi Berkelanjutan di Indonesia - Endhika Hernowo; Iin Suryaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research discusses the role of social and environmental factors in sustainable investment in Indonesia. This research discusses the progress of sustainable investment in Indonesia which is increasingly receiving attention as a response to demands to achieve inclusive economic growth and maintain environmental balance. This research aims to analyze the role of social and environmental factors in the context of sustainable investment in Indonesia. Through a descriptive-analytical approach, researchers investigate how social factors, such as social justice, and environmental factors, such as environmental sustainability, influence investment decisions in various economic sectors. This research uses primary and secondary data to detail the impact of sustainable investment on economic growth, social resilience and environmental conservation. The research results show that the role of social factors, such as local community involvement, and environmental factors, such as environmentally friendly practices, have a positive influence on sustainable investment performance. This research also identifies the challenges and opportunities faced by stakeholders in implementing sustainable investment in Indonesia. These findings provide valuable insights for decision makers, governments and business people in developing sustainable investment strategies that are in line with social values and environmental sustainability. By understanding the complexity of social and environmental factors, it is hoped that sustainable investment can become the main pillar in encouraging sustainable development in Indonesia.